Espaçamento de autovalores e limites superiores para a dinâmica associada a operadores de Schrödinger discretos unidimensionais - Farlei Ferreira Silva (2018)
The goal of this work is to present dynamic upper bounds for boundeddiscrete one-dimensional Schrödinger operators in terms of agglomeration properties of the eigenvalues of finite volume approximations. We discuss an application of these techniques to the Fibonacci Hamiltonian. Such results were originally presented in [4]. We also discuss the possibility of extending them to more general classes of Schr¨odinger operators (such as bounded discrete Dirac operators).